The improved model of user similarity coefficients computation for recommendation systems - Meleshko, Yelyzaveta; Drieiev, Oleksandr; Al-Oraiqat, Anas Mahmoud (Національний технічний університет "Харківський політехнічний інститут", 2020)
The subject matter of the article is a model of calculating the user similarity coefficients of the recommendation systems. The urgency of the development is determined by the need to improve the quality of recommendation systems by adapting the time characteristics to possible changes in the similarity coefficients of users. The goal is the development of the improved model of user similarity coefficients calculation for recommendation systems to optimize the time of forming recommendation lists. The tasks to be solved are: to investigate the probability of changing user preferences of a recommendation system by comparing their similarity coefficients in time, to investigate which distribution function describes the changes of similarity coefficients of users in time. The methods used are: graph theory, probability theory, radioactivity theory, algorithm theory. Conclusions.In the course of the researches, the modelof user similarity coefficients calculating for the recommendation systems has been improved. The model differs from the known ones in that it takes into account the recalculation period of similarity coefficients for the individual user and average recalculation period of similarity coefficients for all users of the system or a specific group of users. The software has been developed, in which a series of experiments was conducted to test the effectiveness of the developedmethod. The conducted experiments showed that the developed method in general increases the quality of the recommendation system without significant fluctuations of Precision and Recall of the system. Precision and Recall can decrease slightly or increase, depending on the characteristics of the incoming data set. The use of the proposed solutions will increase the application period of the previously calculated similarity coefficients of users for the prediction of preferences without their recalculation and, accordingly, it will shortenthe time of formation and issuance of recommendation lists up to 2 times.

Предметом вивчення у статті є модель обчислення коефіцієнтів подоби користувачів рекомендаційних систем. Актуальність розробки визначається необхідністю підвищення якості рекомендаційних систем шляхом адаптації часових характеристик до можливих змін подоби користувачів. Метою є розробка методу визначення періоду стабільності вподобань користувачів рекомендаційної системи на основі перерахунку коефіцієнтів подоби між парами користувачів. Завдання: дослідити ймовірність зміни вподобань користувачів рекомендаційної системи за допомогою порівняння коефіцієнтів їх подоби у часі, дослідити за яким законом розподілу змінюються коефіцієнти подоби користувачів у часі. Методи досліджень:теорія графів, теорія ймовірності, теорія радіоактивності, теорія алгоритмів. Висновки. В ході досліджень вдосконалено модель обчислення коефіцієнтів подоби користувачів рекомендаційних систем. Модель відрізняється від відомих врахуванням показників періоду перерахунку коефіцієнтів подоби для окремого користувача та середнього періоду перерахунку коефіцієнтів подоби для усіх користувачів системи або певної групи користувачів. Розроблено програмне забезпечення, в рамках якого було проведено серію експериментів для перевірки ефективності розробленого методу. Проведені експерименти показали, що розроблений метод в цілому підвищує якість роботи рекомендаційної системи без істотних коливань точності роботи системи. Точність може несуттєво зменшуватись або збільшуватись, залежно від характеристик набору вхідних даних. Використання запропонованих рішень дозволить збільшити період застосування попередньо обчислених коефіцієнтів подоби користувачів для прогнозування вподобань без їх повторного перерахунку та, відповідно, зменшити час формування і видачі рекомендацій до 2 разів.
Вдосконалена модель обчислення коефіцієнтів подоби користувачів рекомендаційних систем
Keywords: collaborative filtering; data analysis; optimization; колаборативна фільтрація; аналіз даних; оптимізація